The Procedural Rules Followed Before the Lease Dispute Settlement Committees and Their Compatibility with the Basic Guarantees and Principles of Litigation in Accordance with Qatari Law (Universitas Negeri Semarang, 2022)
Due to the increase in dealing with lease contracts in the State of Qatar, attention to these contracts and the resulting disputes has been one of the most important priorities of the Qatari lawmaker, especially with regard to the speedy resolution of these disputes, which has a significant impact on achieving justice and stability of transactions within the community. In order to prevent prolonging the litigation period in lease disputes, Law No. (4) of (2008) regarding renting real estate came and established a new phase of litigation procedures in relation to lease disputes through Article (21) thereof, which provided for the establishment of a specialized committee to look into lease disputes called Lease Dispute Settlement Committee. This committee is headed by a judge with the rank of chief from the Court of First Instance chosen by the Supreme Judicial Council. In implementation of this, Cabinet Resolution No (37) of 2008 was issued regarding the rules and procedures to be followed before the lease dispute settlement committees. This study came to clarify these rules and procedures and their role in resolving lease disputes and their reflection on the speed of litigation and their compatibility with the guarantees and basic principles of litigation in accordance with Qatari law.